2019
DOI: 10.1111/acer.14161
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial Examining Cognitive Behavioral Therapy for Individuals With a First‐Time DUI Offense

Abstract: BackgroundDriving under the influence (DUI) programs are a unique setting to reduce disparities in treatment access to those who may not otherwise access treatment. Providing evidence‐based therapy in these programs may help prevent DUI recidivism.MethodsWe conducted a randomized clinical trial of 312 participants enrolled in 1 of 3 DUI programs in California. Participants were 21 and older with a first‐time DUI offense who screened positive for at‐risk drinking in the past year. Participants were randomly ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The proportion of articles consistently using sex terms (χ 2 = 0.09, p = 0.77), consistently using gender terms (χ 2 = 0.10, p = 0.75), and interchangeably using sex and gender terms (χ 2 = 0.57, p = 0.45) did not significantly change from the time period spanning 1997 to 2010 to the time period spanning 2011 to 2021 based on a chi‐square test of difference in proportions (see Figure 2). Of the 123 articles that did not include a sex/gender‐specific sample, only two (1.3%) reported on subgroup analyses to examine whether treatments were differentially effective based on participant sex/gender (in addition to Osilla et al, 2019, which included subgroup analyses based on sex/gender and race/ethnicity, Drislane et al, 2020). Only 18.1% ( n = 28) of articles described concerns regarding sex/gender inclusion or about the generalizability of study findings as a result of their sample's sex/gender composition in their limitations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The proportion of articles consistently using sex terms (χ 2 = 0.09, p = 0.77), consistently using gender terms (χ 2 = 0.10, p = 0.75), and interchangeably using sex and gender terms (χ 2 = 0.57, p = 0.45) did not significantly change from the time period spanning 1997 to 2010 to the time period spanning 2011 to 2021 based on a chi‐square test of difference in proportions (see Figure 2). Of the 123 articles that did not include a sex/gender‐specific sample, only two (1.3%) reported on subgroup analyses to examine whether treatments were differentially effective based on participant sex/gender (in addition to Osilla et al, 2019, which included subgroup analyses based on sex/gender and race/ethnicity, Drislane et al, 2020). Only 18.1% ( n = 28) of articles described concerns regarding sex/gender inclusion or about the generalizability of study findings as a result of their sample's sex/gender composition in their limitations.…”
Section: Resultsmentioning
confidence: 99%
“…Excluding these articles from those considered to have fully reported on their sample's racial/ethnic composition, the number of articles reporting full racial/ethnic information drops from 96 articles (61.9%) to 25 (16.1%). Additionally, no articles (except for Osilla et al, 2019, which included subgroup analyses based on sex/gender and race/ethnicity, Drislane et al, 2020) reported conducting subgroup analyses to examine differences in treatment efficacy across racial/ethnic groups alone, and only 18.1% ( n = 28) of articles mentioned racial/ethnic inclusion (or lack thereof) as a limitation to their study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We will use methods from our previous studies to assess adherence to session content [ 54 , 55 ]. A basic checklist will be developed outlining each session’s content.…”
Section: Methodsmentioning
confidence: 99%